The Potential of Urea Treated Maize Stover for Growth Performance of Weaned Crossbred Calves - Tesfaye Alemu; Pornsri Chairatanayuth; Pravee Vijchulata; Sayan Tudsri (Agriculture and Natural Resources, 2005)
The effects of urea treatment on chemical composition, intake and digestibility of maize stover and the potential of such a stover for growth performance of weaned calves were investigated using 21 crossbred (50% Borana and 50% Friesian) calves of 9 to 12 months of age and an average initial live weight of 138.9 kg. The animals were divided into three groups each of which were individually fed to appetite on basal diets of either untreated maize stover (UNMS), or 5 % urea treated maize stover (UTMS), or natural pasture hay (NPH) for 99 days. In addition, all animals were given 1 kg concentrate mixture per head per day. Urea treatment increased the CP content of maize stover by 3.8 and 2.7 folds over the untreated stover and the natural pasture hay, respectively. Besides, compared with the untreated stover, urea treatment brought an improvement of 9% in in vitro dry matter digestibility and 22% in dry matter intake. These improvements in terms of chemical composition, intake and digestibility led to higher (p<0.05) live weight gain of animals fed on the urea treated stover diet compared with those fed on the untreated stover diet. However, there was no difference (p>0.05) in weight gain between the animals fed on the urea treated stover diet and those fed on the hay based diet. Generally, with the added advantage of being more cost effective than hay, feeding urea treated maize stover may be considered as one of the strategies that bring about an efficient utilization of crop residues for livestock feeding. However, its economic advantage over other alternatives must carefully be examined under the prevailing price conditions before it is implemented.